Therapeutic Use of Acetaminophen and Light to Moderate Alcohol: Are There Early Disparate Risks for Kidney Disease? (Mary Ann Liebert, 2020)
Introduction: Acetaminophen (APAP) is the most common medication taken in the United States. Using the 2003?2004 U.S. National Health and Nutrition Examination Survey (NHANES), the authors previously explored and reported the relationship of concomitant consumption of light to moderate alcohol (LMA) and therapeutic doses of APAP to early risk of renal dysfunction among adults in the United States. Statistically significant increased odds of renal dysfunction were noted among respondents who reported use of therapeutic doses of APAP and LMA by adjusting for hypertension, diabetes, and obesity. In this study the authors explored further on of potential disparities in the above relationship in the population. The relationship was verified with the 2009 Chronic Kidney Disease?Epidemiology Collaboration creatine-based estimated Glomerular Filtration Rate (GFR). Methods: Subgroup logistic regression analyses to assess disparities based on gender, race, age, education, and income were performed for renal dysfunction measured in terms of serum creatinine (SCr) directly as well as self-report using NHANES 2003?2004 data. Results: Early stage renal dysfunction, as determined by self-reports, and SCr and GFR values may occur among those who concomitantly ingested therapeutic doses of APAP and described alcohol use when compared to those who do not. Risks were more profound among females, particularly in minority racial groups, below legal drinking age of 21, and with household income below $25K. Conclusion: Potential risks for renal dysfunction are apparent in a disparate manner resulting in possible health inequity. Further research could increase the sample size of minority groups and specifically assess for effect modifiers that NHANES does not include for assessment.